Impairment of Cognitive Function Increases Mortality Risk in Relation to Cardiac Sympathetic Denervation and Renal Dysfunction in Patients With Systolic Heart Failure - Nabuchi, Mirei; Doi, Takahiro; Hatano, Ryosuke; Tsuzuki, Taro; Komuro, Kaoru; Iwano, Hiroyuki; Nagahara, Daigo; Yuda, Satoshi; Hashimoto, Akiyoshi; Nakata, Tomoaki (Circulation Journal, 2024)
Background: In contrast to the well-known prognostic values of the cardiorenal linkage, it remains unclear whether impaired cognitive function affects cardiac prognosis in relation to cardiac sympathetic innervation and renal function in patients with heart failure (HF).Methods and Results: A total of 433 consecutive HF patients with left ventricular ejection fraction (LVEF) <50% underwent the Mini-Mental State Examination (MMSE) and a neuropsychological test for screening of cognition impairment or subclinical dementia. Following metaiodobenzylguanidine (MIBG) scintigraphy, patient outcomes with a primary endpoint of lethal cardiac events (CEs) were evaluated for a mean period of 14.8 months. CEs were documented in 84 HF patients during follow-up. MMSE score, estimated glomerular filtration rate (eGFR) and standardized heart-to-mediastinum ratio of MIBG activity (sHMR) were significantly reduced in patients with CEs compared with patients without CEs. Furthermore, overall multivariate analysis revealed that these parameters were significant independent determinants of CEs. The cutoff values of MMSE score (<26), sHMR (<1.80) and eGFR (<47.0 mL/min/1.73 m2) determined by receiver operating characteristic (ROC) analysis successfully differentiated HF patients at more increased risk for CEs from other HF patients.Conclusions: Impairment of cognitive function is not only independently related to but also synergistically increases cardiac mortality risk in association with cardiac sympathetic function and renal function in patients with HF.